Diverse Response of Western North Pacific Anticyclone to Fast‐Decay El Niño During Decaying Summer. Issue 7 (4th April 2023) - Jiang, Leishan; Chen, Han‐Ching; Li, Tim; Chen, Lin
Abstract: Previous studies suggested that fast‐decay El Niño events are more favorable in generating the western North Pacific anticyclone (WNPAC) in the decaying summer. However, we found that this is not the case for all fast‐decay El Niño events. By comparing two groups of fast‐decay El Niño events with significant and insignificant WNPAC in the following summer, we found that the westward extension of the equatorial Pacific cold sea surface temperature anomalies (SSTA) and the subtropical central‐north Pacific cold SSTA play important roles in the generation and intensification of the WNPAC during decaying summer. Further analyses indicated that the internal atmospheric mode—North Pacific Oscillation during boreal spring can affect the formation of the cold SSTA over the subtropical central‐north Pacific and the westward extension of the equatorial Pacific cold SSTA during summer. Additional effects of tropical Indian and Atlantic forcing on the maintenance of the WNPAC are also shown. Plain Language Summary: The boreal summer western North Pacific anticyclone (WNPAC) is an important low‐level circulation over the western Pacific, which can have great impacts on the East Asia climate. Previous studies pointed out that the fast‐decay El Niño events are favorable in inducing the WNPAC in the decaying summer. However, our observational and modeling results suggested that not all the fast‐decay El Niño events can generate WNPAC in the decaying summer. By dividing fast‐decay El Niño events into two groups, one with significant WNPAC in the following summer and the other without, we found that the difference in the equatorial Pacific cold sea surface temperature anomalies (SSTA) westward extension, the subtropical central‐northern Pacific cold SSTA and the tropical Indian/Atlantic warm SSTA are important in causing the diverse response of the WNPAC to the fast‐decay El Niño events during decaying summer. Further analyses indicated that the internal atmospheric mode—North Pacific Oscillation during boreal spring can affect the cold SSTA over the subtropical central‐north Pacific and the westward extension of the equatorial Pacific cold SSTA during boreal summer. The tropical Indian and Atlantic warming, can also directly influence the WNPAC intensity or feedback to the equatorial and subtropical Pacific cooling to influence the WNPAC. Key Points: Fast‐decay El Niño is more favorable in generating western North Pacific anticyclone (WNPAC) in the decaying summer but this is not the case for all fast‐decay El Niño Equatorial Pacific, subtropical Pacific cold sea surface temperature anomalies (SSTA) and tropical Indian/Atlantic warm SSTA in summer are key to the diverse response of WNPAC The spring North Pacific Oscillation is important in causing the diverse equatorial and subtropical Pacific cold SSTA forcing in summer